2012
DOI: 10.1590/s0102-05362012000300026
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da lâmina de irrigação na conservação pós-colheita de melão Pele de Sapo

Abstract: Sabe-se que há influência das condições de cultivo na qualidade e conservação pós-colheita dos frutos, sendo escassos na literatura os trabalhos que relacionem o uso de lâmina de irrigação com a qualidade e conservação pós-colheita do melão. Assim, objetivou-se avaliar o efeito da lâmina de irrigação na conservação pós-colheita de melão Pele de Sapo. Para isto, conduziu-se um experimento em uma área localizada no município de Mossoró (RN), de setembro a dezembro de 2004. O ensaio consistiu do plantio do meloei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The decrease in the SS content according to the increase of irrigation depth may be related to the reduction in the concentration of the elements that originate mainly sugars, due to the higher availability of water in the plant and, therefore, in the fruits (Araújo and Botrel, 2010). Medeiros et al (2012) did not observe a significant change in the soluble solids content in melon fruits due to the irrigation depths. Dantas et al (2011) evaluated the effect of irrigation depths and soil mulching with different types of polyethylene films and uncovered soil in melon crop and observed that the higher irrigation depth, the higher SS values.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The decrease in the SS content according to the increase of irrigation depth may be related to the reduction in the concentration of the elements that originate mainly sugars, due to the higher availability of water in the plant and, therefore, in the fruits (Araújo and Botrel, 2010). Medeiros et al (2012) did not observe a significant change in the soluble solids content in melon fruits due to the irrigation depths. Dantas et al (2011) evaluated the effect of irrigation depths and soil mulching with different types of polyethylene films and uncovered soil in melon crop and observed that the higher irrigation depth, the higher SS values.…”
Section: Resultsmentioning
confidence: 87%
“…The highest averages of fruit texture were found in the irrigation depth of 85% ETc, with the soil mulching with polyethylene film (426.25 cN) and with rice straw (435.00 cN). Fruits harvested with greater firmness of the pulp generally have greater conservation and postharvest shelf life, because the firmer fruits are more resistant to mechanical injuries during transport and commercialization (Medeiros et al, 2012;Martínez-Valdivieso et al, 2015). Medeiros et al (2012) observed that pulp firmness of melon decreased with the increase in irrigation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations